Incorrect Use of Antibiotics - Asmaa Khalid Salman (Journal of Global Pharma Technology, 2016)
The present study aims to determine the information about the safe and appropriate antibiotic which can be utilized among the undergraduate students of medical and dental colleges. The formula that was applied in the current study was an integrated self-administration approach. We found that dental students were more aware of the instructions provided by the doctor. They resorted to specialized assistance from healthcare professionals. Nevertheless, the observed difference between males and females in the medical profession in this study was significant where the females were more aware of self-medication compared to males. Furthermore, The findings of this research provide evidence about the self-medication prevalence. There was a sudden increase in the misuse of antibiotics other than being used for medicinal purposes. In dealing with this challenge, relevant healthcare bodies can play an important role in ensuring that self-medication is curbed through effective regulatory mechanisms. At the same time,  they can offer information about the proper use of medications and various kinds of prescriptions.Keywords: Self-medication, Dental students, Antibiotic resistance.